1972
DOI: 10.1037/h0032678
|View full text |Cite
|
Sign up to set email alerts
|

The use of observationally presented information to modify hypnotic susceptibility.

Abstract: This study examined the extent to which hypnotic susceptibility could be modified by means of various types of information modeled on a videotape. Of particular interest was the extent to which hypnotizability could be altered for the initially less susceptible S. Two major informational components were compared: (a) behavioral modeling cues, in which 5s observed a model acquiesce to seven hypnotic suggestions, and (6) verbal modeling cues, in which information was presented designed to correct misconceptions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
50
2

Year Published

1976
1976
1996
1996

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 12 publications
9
50
2
Order By: Relevance
“…In contrast to the stable trait view, a substantial number of studies conducted in several different laboratories now indicate that cognitive skill training programs that are aimed at enhancing positive attitudes toward hypnosis, and that provide subjects with appropriate strategies and interpretations, can produce large increments on both behavioral and subjective indexes of hypnotizability [4][5][6][7][8][9]. For example, Gorassini and Spanos [6] developed a single session, three component skill training procedure (the Carleton Skill Training Package: CSTP) designed to enhance positive attitudes toward hypnosis, teach imagery strategies for experiencing subjective effects called for by suggestions, and inculcate an active interpretational set toward test demands.…”
mentioning
confidence: 91%
“…In contrast to the stable trait view, a substantial number of studies conducted in several different laboratories now indicate that cognitive skill training programs that are aimed at enhancing positive attitudes toward hypnosis, and that provide subjects with appropriate strategies and interpretations, can produce large increments on both behavioral and subjective indexes of hypnotizability [4][5][6][7][8][9]. For example, Gorassini and Spanos [6] developed a single session, three component skill training procedure (the Carleton Skill Training Package: CSTP) designed to enhance positive attitudes toward hypnosis, teach imagery strategies for experiencing subjective effects called for by suggestions, and inculcate an active interpretational set toward test demands.…”
mentioning
confidence: 91%
“…More-38 SAAVEDRA AND MILLER over, most experimental manipulations of hypnotic expectations have been so indirect in nature that there is some doubt as to whether it was expectations or some other variables that were, in fact, being examined. For example, procedures for the manipulation of expectations have included exposure to different models (Brown & Krasner, 1969;Klinger, 1970); experiencing of suggestions during an imagination condition (Wilson, 1968); provision of information regarding the nature of hypnosis (Barber & Calverley, 1964;Diamond, 1972); and use of posthypnotic suggestions (Gandolfo, 1971). In general, these studies have shown that hypnotic susceptibility can more readily be reduced with the provision of negative expectations than increased with positive expectations.…”
mentioning
confidence: 99%
“…A parallel result has been reported by Shor and Orne (1962) An additional factor which may have contributed to higher SHSS:A scores was that all subjects in the present study were routinely exposed to a lecture intended to dispel myths and misconceptions about hypnosis. There is evidence (e.g., Diamond, 1972;Reilleyet aI., 1980) that exposure to this type of information does increase susceptibility scores. All in all, subjects in the present study were above average in susceptibility and therefore conclusions should be limited to volunteer populations.…”
Section: Resultsmentioning
confidence: 95%